1975
DOI: 10.1016/s0022-5347(17)59432-x
|View full text |Cite
|
Sign up to set email alerts
|

Renal Pelvic Tumors

Abstract: A study was made of 35 patients with tumors of the renal pelvis. Tumors were indipendently graded and staged by a newly proposed method. The method of staging correlated well with grading of renal pelvic tumors and bore a direct relationship with prognosis. The high incidence of associated urothelial tumors, especially on the involved side, mandated radical nephroureterectomy including a bladder cuff as the treatment of choice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
5
0

Year Published

1976
1976
2009
2009

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(7 citation statements)
references
References 6 publications
2
5
0
Order By: Relevance
“…However, unlike the majority of urothelial neoplasms of the bladder which are noninvasive at presentation, 37 many studies of renal pelvic tumors have shown that most patients present with invasion, with only a 3.5-34% incidence of noninvasive disease. 14,15,19,[22][23][24]38,39 In our analysis and others, 20 a significantly greater number of cases demonstrated low-stage disease than highstage disease (69% rpT1 disease vs 31% ZpT2 disease), which closely approximates the 70% of bladder tumors which are 'superficial' (pTa, pTIS, pT1) at presentation. 36,37 In two more recent series of renal pelvic tumors, Gomez et al 38 and Olgac et al 39 also reported that a slightly greater number of tumors were low stage (rpT1) than high stage.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…However, unlike the majority of urothelial neoplasms of the bladder which are noninvasive at presentation, 37 many studies of renal pelvic tumors have shown that most patients present with invasion, with only a 3.5-34% incidence of noninvasive disease. 14,15,19,[22][23][24]38,39 In our analysis and others, 20 a significantly greater number of cases demonstrated low-stage disease than highstage disease (69% rpT1 disease vs 31% ZpT2 disease), which closely approximates the 70% of bladder tumors which are 'superficial' (pTa, pTIS, pT1) at presentation. 36,37 In two more recent series of renal pelvic tumors, Gomez et al 38 and Olgac et al 39 also reported that a slightly greater number of tumors were low stage (rpT1) than high stage.…”
Section: Discussionsupporting
confidence: 70%
“…The prognosis of patients with these tumors has repeatedly been shown to depend on the tumor stage and grade. [9][10][11][13][14][15][17][18][19][21][22][23][24] At nephrectomy, our study group was divided nearly equally into those with noninvasive disease and those with an invasive component ( Table 2). Nielsen and Ostri 21 in their study of primary tumors of the renal pelvis had a slightly greater percentage (56%) of noninvasive tumors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pathological stage, grade, multiplicity of the tumor and synchronous or metachronous bladder carcinoma have been reported to be prognostic factors of upper tract urothelial carcinoma [11, 12, 13, 14, 15]. Our results showed that lymph node metastasis was the only independent and significant prognostic factor revealed by multivariate analysis using Cox’s proportional hazards model.…”
Section: Discussionsupporting
confidence: 51%
“…The most widely used staging system for renal pelvic transitional cell carcinoma (renal pelvic cancer) is that of Grabstald et d.,' and other staging systems have subsequently been described (Table l). [2][3][4][5] In general, renal pelvic cancer staging systems have the disadvantage of being based on a bladder cancer model6 because both are urothelial malignancies. Although histologically similar, they are anatomically and biologically dissimilar.…”
Section: Renal Pelvic Transitional Cell Carcinomamentioning
confidence: 99%